ANALYSIS OF THE ADDITION OF COMMERCIAL ORGANIC SULFUR COMPOUNDS AT DIFFERENT DOSES ON THE GROWTH RATE AND SURVIVAL RATE OF BARRAMUNDI (Lates calcarifer) - Wulandari, Putu Desi Kusuma; Sitepu, Gressty Sari br.; Amelia, Jasmine Masyitha (Jurusan Perikanan dan Kelautan, 2025)
Barramundi (Lates calcarifer) is a euryhaline carnivorous fish species. The nursery phase often poses a major challenge in its aquaculture development. Common issues at this stage include stress-prone fry, feed residues that degrade water quality, high stocking densities, disease outbreaks, and low feed quality, which can lead to nutrient deficiencies and mortality. A potential solution is supplementing feed with commercial organic sulfur compounds. These compounds are chemical groups containing sulfur atom chains and naturally occur in garlic. This research uses an experimental method with a Completely Randomized Design (CRD), consisting of 4 treatments and repeated 3 times. The treatments consisted of P0 (Control), P1 (Commercial organic sulfur compounds at 1 ml/kg), P2 (Commercial organic sulfur compounds at 3 ml/kg), P3 (Commercial organic sulfur compounds at 5 ml/kg). The experiment was conducted over 25 days. Data analysis was performed using One Way ANOVA with Tukey’s post-hoc test. The results showed that barramundi (L. calcarifer) fed with P1 (1 ml/kg organic sulfur compound supplementation) exhibited the best growth performance with absolute length growth (5.79 cm), absolute wight growth (4.96 g), specific growth rate (0,1985%). However, the supplementation had no significant effect on survival.